Scientific Software: Legacy Software Maintenance - Mendez, Mariano (Journal of Computer Science & Technology, 2016)
Software production and maintenance is one of the most widely studied topics in computer science. Taking into account that scientists were the first ones to perform this task, even before the Computer Science discipline obtained its name, scientific software production still remains a challenge. This phenomenon may stem from the fact that some authors realized that there is a "gap" between scientific production techniques and industry software techniques [1]. This research work is founded on two relevant contributions to this subject. The first one, the Aristotelian analysis performed by Frederick Brooks on software essence that has been beautifully described in [2]. The second one was proposed by Ralph Johnson in his article "Software development is program transformation." Based on these two great contributions, Change- Driven Development is proposed as a new agile methodology born as a new approach to maintain and develop Scientific Software.